Church presence and gender relations in the Wonenara valley (Eastern Highlands Province, Papua New Guinea). (21st April 2016) - Bonnemère, Pascale
Abstract : Since 1951, date of the First contact, the Baruya of the Wonenara valley have twice been a pioneering frontline for Protestant missions. First in the 1960s, when several Lutheran and SDA pastors moved in, and the second time at the beginning of the 2000s, when three 'New Evangelical Churches' settled in the valley. After presenting the history of the presence of these five Churches, I analyse the pastors' ideas, as expressed during services or in informal discussions, about the place of women in daily life and in church, and about gender relations more generally. The observation of church services reveals a possibility of women speaking in public that was hitherto unknown. Moreover, the pastors' origins (Baruya or non Baruya) seem to play a role in the way they talk about women during their services, whatever their Church may say.